Factors associated with exclusive breastfeeding in "Near Miss" neonates in Brazil - Daniele Marano; Theonas Pereira; Yasmin Amaral; Vania De Matos Fonseca; Maria Elisabeth Moreira (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2024)
Abstract Objective To assess the association between sociodemographic and perinatal factors and hospital practices to encourage exclusive breastfeeding in near miss neonates in maternity hospitals. Methods This is a prospective cohort of live births from the survey "To be born in Brazil" conducted between 2011 and 2012. The weighted number of newborns who met the neonatal near miss criteria was 832. Exclusive breastfeeding at hospital discharge and 45 days after delivery were dependent variables of the study. The sociodemographic and perinatal factors of the puerperal women and hospital practices to encourage breastfeeding were independent variables. The data were analyzed with Poisson regression and set with p value<0.05. Is exclusive breastfeeding in neonatal near misses associated with factors related to sociodemographic conditions, maternal characteristics and the organization of health services? Results Data from 498 women and their children were analyzed. Mothers with incomplete primary education were more likely (36%) to have exclusive breastfeeding (RR: 1.36; 95% CI: 1.06-1.74) at discharge. Women who did not offer the breast to the newborn in the joint accommodation (65%) were less likely to be breastfeeding exclusively (RR: 0.65; 95% CI: 0.56-0.75) at discharge. Variables that increased the probability of exclusive breastfeeding after 45 days of delivery were primiparity (RR: 1.36; 95% CI: 1.08-1.69) and having the newborn in the delivery room (RR: 1.90; 95% CI: 1.12-3.24). Conclusion Exclusive breastfeeding in neonatal near misses was associated with maternal characteristics and important hospital practices, such as being breastfed in the joint accommodation and the newborn being in the mother's lap in the delivery room.